COHESION IN STUDENTS’ SPEECHES - Maryati, Sri; Suprapti, Sri (ELT Forum: Journal of English Language Teaching, 2018)
Cohesion is the first criterion of textuality which is very important because it is thelinks that hold text together and give it meaning. This study aims to identify whetherthe speeches produced by English major sophomores are cohesive or not and todescribe the kinds of cohesive devices found in the speeches. The object of this studyis the speeches produced by the third semester students of English Department,which then were transcribed into written. The data collected were analyzed based ondiscourse analysis using cohesive devices based on Halliday and Hasan‟s theory(1976). The findings show that there are 1040 ties found in the ten speeches whichreveals that the five types of cohesive devices occur in the speeches although thedistribution of each type is significantly different. Based on the findings, it can beconcluded that the ten speeches are cohesively produced. In addition, all of fivetypes and sub-types of cohesion are found in the monologues except verbal ellipsis.